Cone angle control of the interaction of magnetic clouds with the Earth's bow shock. Issue 10 (27th May 2016) - Turc, L.; Escoubet, C. P.; Fontaine, D.; Kilpua, E. K. J.; Enestam, S.
Abstract: We study the interaction of magnetic clouds (MCs) with the near‐Earth environment. Recent works suggest that the bow shock crossing may modify significantly the magnetic structure of an MC, and thus its ability to drive geomagnetic storms. This change is largely controlled by the bow shock configuration, which depends on the upstream interplanetary magnetic field (IMF) orientation. From the distribution of the magnetic field orientation in 152 Earth‐impacting MCs, we determine for the first time the typical shock configuration during MC events. We find that 56% (6.3%) of the time, the subsolar bow shock configuration is exclusively quasi‐perpendicular (quasi‐parallel). The rest of the time, both configurations coexist. Furthermore, using a subset of 63 MCs observed simultaneously in the solar wind and in the dayside magnetosheath, we determine the magnitude of the magnetic field alteration, how it depends on the shock configuration, and how it relates to the IMF cone angle. Key Points: The typical bow shock configuration encountered during magnetic clouds is investigated using 152 Earth‐impacting events We find that 56% (6.3%) of the time, the subsolar bow shock configuration is exclusively quasi‐perpendicular (quasi‐parallel) during MCs The upstream cone angle controls the shock configuration and the alteration of the magnetic field orientation across the bow shock